Digital geographies - Ash, James, active 2019; Kitchin, Rob; Leszczynski, Agnieszka (London : SAGE Publications Ltd, 2019)
As digital technologies have become part of everyday life, mediating tasks such as work, travel, consumption, production, and leisure, they are having increasingly profound effects on phenomena that are of immediate concern to geographers. These include: the production of space, spatiality and mobilities; the processes, practices, and forms of mapping; the contours of spatial knowledge and imaginaries; and, the formation and enactment of spatial knowledge politics Similarly, there are distinct geographies of digital media such as those of the internet, games, and social media that have become indispensable to geographic practice and scholarship across sub-disciplines, regardless of conceptual approach. This textbook presents a fully up-to-date, synoptic and critical overview of how digital devices, logics, methods, etc are transforming geography. It is divided into six inter-related sections {u2022} introduction to digital geographies {u2022} digital spaces {u2022} digital methods {u2022} digital cultures {u2022} digital economies {u2022} digital politics With illustrious instructors and researchers contributing to every chapter, Digital Geographies is the ideal textbook for courses concerning digital geographies, digital and new media and Internet communications, and the spatial knowledge of politics.
Includes bibliographical references and index.
Description based on XML content.
Keywords: Digital media; Geography